Pengaruh Latihan Senam Kaki Diabetes Terhadap Sensitivitas Kaki pada Penderita Diabetes Mellitus Tipe II - Aulia Rahman; Sri Maryuni; Anisa Dwi Rahmadhani (Jurnal Keperawatan Profesional (KEPO), 2021)
Diabetes mellitus is a disease caused by a relative or absolute lack of insulin. The complications experienced by people with diabetes mellitus are changes in the peripheral nervous system, namely peripheral neuropathy or impaired sensitivity of the legs. The purpose of this study was to determine the effect of giving foot gymnastics on foot syncsitivity in type II diabetes mellitus sufferers in the work area of ??the central Yosomulyo Metro Health Center 2019. The research design used a pre-experimental one group pretest-posttest design, the population in this study was 198 people. The sample used was 21 people with the sampling technique using purposive sampling. The analysis in this study used the t-test. The results of statistical tests showed that the average foot sensitivity score of type 2 diabetes patients before treatment was 2,48-1,123 and after 3,38-1,244 with the average difference between the scores before and after treatment was 0,905, 50,539; p-value 0,000 (p <50,05) means that there is an effect of giving foot exercises on the sensitivity of the feet in people with diabetes mellitus type 2. For diabetes mellitus sufferers, they must be able to do regular foot exercises so that blood circulation in the legs is smooth and does not experience peripheral neuropathy so that can avoid canker sores.